Imagined Authenticity The Somatic Semiotics of Global "Koreanness" - Elfving-Hwang, Joanna (University of Minnesota Press, 2024)
This article examines how the somatic aspects of K-pop aesthetics, and in particular stage aesthetics adapted by K-pop idols, have emerged as recognizable signs of representing "global Koreanness" outside of Korea. While the use of cosmetics, fashion, and other technologies of the body such as fillers and cosmetic surgery are rarely associated with ideas of bodily authenticity, this article examines the ways in which the K-pop and K-beauty aesthetics more broadly have emerged as a recognizable style, and consider how the semiotics of the body on stage for global gaze intersect with both cultural nationalism and the idea of an authentic "global Koreanness" that renders ethnic nationalism palatable and desirable for global consumption. By focusing on how ethnic Koreanness is utilized to emphasize the desirability of K-pop and a K-pop aesthetic, the links between ethnic nationalism in Korea, and how the project of promoting "authentic global Koreanness" is reinforced by fans. The potential for this aesthetic to challenge global beauty cultures and ideals as racialized and dominated by white middle-class beauty in the industrial West is undermined by such discursive construction of global K-pop idols as racialized symbols of national identity.